A needs assessment survey of dental public health graduate education in Saudi Arabia - Dania Ebrahim Al Agili (Saudi Dental Journal)
Objectives: The Faculty of Dentistry at King Abdulaziz University (KAU) is planning to develop a master’s program in dental public health (DPH). To develop a curriculum for this program, a needs assessment was conducted in order to identify the level of DPH expertise that currently exists in Saudi Arabia, to identify gaps in knowledge, and to explore current perceptions regarding this type of program. Methods: A competency-based survey instrument was administered to private and government affiliated dental practitioners in Jeddah, Saudi Arabia. Participants’ knowledge, attitudes, and competencies in DPH were assessed. In addition, questions were submitted that addressed preferred strategies of teaching, curriculum delivery methods, course content, and prerequisites for DPH. These data were combined with data previously collected from dentists holding academic positions at KAU (n = 146) and were analyzed using Statistical Analysis System version 9.3 software. Mean values and frequencies were calculated for the study variables. Proportional odds ratios and 95% confidence intervals were estimated to assess differences in educational preferences and DPH competencies according to age, gender, and qualification. Results: Most of the participants (95%) reported a need for a DPH graduate program. The respondents had a basic knowledge of DPH and moderate experience in DPH competencies. A variety of preferred educational strategies and methods were identified and differences in educational preferences according to age, gender, and qualification of the respondents were identified. The responses obtained also acknowledged skills and competencies that the participants considered most important for a DPH practice and that would be important for students accepted into a DPH graduate program. Conclusions: This needs assessment survey represents a preliminary step in establishing a DPH graduate program that addresses current gaps in knowledge and in the practice of public health dentistry. This survey also provided valuable feedback regarding the development of course content for a graduate education program in DPH. Keywords: Public health dentistry, Community dentistry, Dental health education, Dentistry, Saudi Arabia